ANALYSIS OF THE LIFESTYLE PROFILE OF THE BENEFICIARIES OF A PORTO ALEGRE-RS CLUB (Fiep Bulletin - online, 2017)
The present study aims to analyze the lifestyle of the beneficiaries of a Porto Alegre-RS club. The sample consisted of47 recipients of both sexes, aged between 14 and 70 years. The research instrument used was the Nahas Individual LifestyleProfile questionnaire (2000). The life habits adopted by this group of beneficiaries were considered satisfactory among the fivecomponents of the lifestyle analyzed. Very satisfactory result in the nutrition component since 29.8% of the respondents statedavoiding the intake of fats and sweets at times. Regarding physical activity, 46.8% stated that they always practice moderateactivities. In the preventive behavior the result was positive, since 66.0% of the interviewees always affirm to control their bloodpressure and cholesterol levels. In the social relationship, 89.4% of the beneficiaries are satisfied with their social relationshipsand 68.1% say that they include diversified activities with their friends at their leisure. Negative result in stress control, since44.7% of the interviewees reserve daily time for rest. In this way, it is important to emphasize the importance of good eating habits,to seek to do moderate physical activities to maintain physical abilities, to seek to maintain health in order to prevent illness, tomaintain an active social relationship and always to take time to rest. Developing a better quality of life.